(untitled) (Journal of Hama University, 2025)
The research aimed to identify the most important strategies to recover and compensate for educational loss that were applied when the educational process had resumed after the Corona pandemic, in basic education schools in the city of Latakia, the most important difficulties and obstacles faced, and finding the most important practical solutions to confront similar crises. To achieve the research objectives, the descriptive approach was used, and a questionnaire was designed that consisted of (22) items divided into two axes (applied strategies) and (difficulties and obstacles), in addition to an open question about the proposed solutions.The research sample included (223) male and female teachers for the academic year 2022/2023.The research concluded with the most important results, which are: applying compensation strategies to a degree that ranged between medium and high, according to the opinions of the research sample, and that the scarcity of electricity and the weakness of the Internet network were among the most prominent difficulties facing the compensation process, and one of the most prominent solutions proposed was: Forming a team of teachers dedicated to work in educational crises.